16Performance, Theater, Drama. (14th September 2019) - Kastleman, Rebecca
Abstract: The year 2018 was an especially fruitful and wide-ranging one for theater and performance studies. Several major monographs deepened discussion in established subject areas within the field, while new methodological approaches emerged, opening fresh directions in scholarship. This review focuses on four major areas of conversation that shaped the field in 2018: 1. Expanding Performance Aesthetics; 2. Economic and Material Contexts of Performance; 3. Enacting Public Justice; and 4. Performance on the Move.